MANAJEMEN RISIKO PADA UMKM DI INDONESIA - Abdul Majid, Muhamad; Ni’mati Rahmatika, Arivatu; Suprayogi, Agus (LPPM Universitas KH. A. Wahab Hasbullah, 2019)
Abstract: MSMEs are small, labor-intensive businesses that involve a lot of economic and business activities in terms of technology, management, investment and copyright protection. Therefore this research was compiled with the aim of knowing how to overcome or manage various kinds of risks that occur in a business. The research method used is the type of literature review. Risk management aims to manage risk so that optimal results in a business or activity can be achieved. Risk management is basically carried out through processes consisting of 3 stages as follows: 1). Doing Risk Identification, 2). Risk Evaluation and Measurement, and 3). Risk management. Keywords: Risk management, MSMEs